Influence of different light sources on visual shade matching performance - Romina Roodgarian; Tolo Jafari; Soraya Khafri; Faezeh Abolghasemzadeh (Babol University of Medical Sciences, 2016)
Introduction: The shade selection ability of dentists is a necessary element in natural tooth color recreation. Visual shade selection is affected by light source variables. The aim of this study was to compare the results of shade matching under three light conditions. Materials &Methods: The Ishihara test was doneon58 volunteers participated in this study: 40 dental interns, 10 Postgraduate students of restorative dentistry, 8 Postgraduate students of prosthodontics. Totally, 9 classical vita shade tabs were randomly chosen and their codes were covered. The participants matched these 9 shades with a complete classical vita shade under the lighting condition in the dental office, natural light and corrected light source. Matching scores were computed and the mean of the color differences between the citation shades and the chosen shades counted with ΔEab* formula. The data were analyzed using Mann-Whitney, Friedman and Wilcoxon test. Results: The average of shade matching scores with correcting light (7.87) was higher than the lighting conditions in the dental office (3.94) and natural light(5.53). Comparison of ΔE between three light conditions was significant (P<0.05). No significant difference was found in shade matching scores by sex (P>0.05).There was a significant difference between scores of under-graduate and post-graduate students (P<0.05). Conclusion: To achieve successful shade matching, it is recommended to use the corrected light source. The combination of using corrected light and training can improve shade matching performance.